Effectiveness of the SQ3R Method in Improving Students' Reading Ability in MTS - SALSABILA, Jihan Hasna (Community Services: Sustainability Development, 2025)
This study focuses on reading training for students who cannot read yet in class VII D MTs Negeri 5 Karanganyar, conducted by Internship participants. This training aims to improve students' reading skills through reading. This training is expected to benefit students in developing reading skills. Students are also given reading materials appropriate for their class level, namely class VII. Of the 3 students who participated in the reading training program, an average reading ability of 57% was obtained, in the sufficient category. The teacher's response to the implementation of the reading training program was 83% with a Satisfied category, while the response of class VIID MTs Negeri 5 Karanganyar students to the implementation of the reading training program was 65% with a moderate category. The results of this activity indicate that effective reading training strategies can help students improve their reading skills, this can be seen from the good responses given. The implementation of this reading training program shows promising results, as it has effectively supported the development of students' reading skills. Through structured practice and the use of appropriate reading materials, students' engagement and progress have been notable. Future improvements could involve tailoring materials further to the diverse needs of students, ensuring that the training continues to foster a more significant impact on their overall literacy development. Additionally, continued collaboration with teachers could enhance the program's effectiveness.